The Relationship between Electricity Consumption, Foreign Direct Investment and Economic Growth: Case of Benin - Atchike, Desire Wade; Zhao, Zhen-Yu; Bao, Geriletu (International Journal of Energy Economics and Policy, 2020)
Using the autoregressive distributed lag (ARDL) bounds test with dummy variables and the Toda-Yamamoto approach; this paper investigated the relationship between electricity consumption, foreign direct investment and economic growth in Benin for the period of 1980-2014. Confirming the growth theory for Benin, the results show evidence of unidirectional causalities from electricity consumption to both economic development and foreign direct investment and a long run relationship with a speed of adjustment of 60.72%. These findings suggest that the government of Benin should target the implementation of new strategies to improve access to electricity in order to attract more foreign investment and achieve a rapid and sustainable economic growth. Keywords: Electricity Consumption, Foreign Direct Investment, Economic Growth, Benin. JEL Classifications: F21, F43, Q43. DOI: https://doi.org/10.32479/ijeep.9415